If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 4 = 7x + 69 Reorder the terms: 4 + -6x = 7x + 69 Reorder the terms: 4 + -6x = 69 + 7x Solving 4 + -6x = 69 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 4 + -6x + -7x = 69 + 7x + -7x Combine like terms: -6x + -7x = -13x 4 + -13x = 69 + 7x + -7x Combine like terms: 7x + -7x = 0 4 + -13x = 69 + 0 4 + -13x = 69 Add '-4' to each side of the equation. 4 + -4 + -13x = 69 + -4 Combine like terms: 4 + -4 = 0 0 + -13x = 69 + -4 -13x = 69 + -4 Combine like terms: 69 + -4 = 65 -13x = 65 Divide each side by '-13'. x = -5 Simplifying x = -5
| 12y-10=3x+6x | | (7x+4)+(5x+3)+(2x+5)= | | 6x=6k+2k | | 100=5x+15 | | 28=6z-2 | | 6(-2x+7)=66 | | 2m=-3m+-3 | | 7x+9+2x=6x-18 | | 3=2j-7 | | 5y+5=7y-7 | | -4x+3=21 | | 3(x-1)+2x=7 | | 4v+8=44 | | W-11=11 | | 12+5x=1+4x+3 | | -4+3=21 | | -2(-9+6x)=-18 | | -2y+24=30 | | 18=8+2h | | 31=3u+10 | | 5x^2+18x+-8=0 | | -133+10x=-7x+91 | | 23-c=21 | | -7x+8=-6x+9 | | -84=-7(p-2)-7p | | 49a^2-70a+25=0 | | -7x+4=22-4x | | 3(9+2x)=21 | | 7x+9-4x=15 | | y+9=6-2y | | 35-x-24= | | 3x-2+4-x=-4 |